Neonatal Intractable Seizures and Valproic acid Therapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Seizures resistant to phenobarbital were controlled in four of six neonates by valproic acid (VPA) monotherapy and in one with polytherapy at the Moses H Cone Memorial Hospital, Greensboro, NC.